Insuring Public Finances Against Natural Disasters : A Survey of Options and Recent Initiatives - Hofman, David (IMF Working Papers; Working Paper ;, 2006)
Natural disasters can put severe strain on public finances, in particular in developing and small countries. But catastrophe insurance markets increasingly offer opportunities for the transfer of such risks. Thus far, developing countries have only tepidly begun to tap these opportunities. More frequent and intensive use of insurance markets may be desirable because it could help introduce an important element of predictability in the post-disaster public finances of disaster-prone developing countries. Against this background, the paper surveys the various available insurance modalities and reviews recent initiatives in developing and emerging market countries. It also identifies some key challenges for the insurance community, donors, and international financial institutions (IFIs).